Thyroid Function and ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Routine thyroid function studies in a community referred sample of boys with ADHD were examined for evidence of generalized resistance to thyroid hormone at the National Institute of Mental Health, Bethesda, MD.